Globalisation hits the cloud barrier. (May 2015) - Jarvis, Adam
Abstract : Globalisation is now an accepted fact of life. Nobody these days is surprised to see Coca Cola on sale in Chengdu or a Big Mac in Moscow. However, suddenly, with the emergence of cloud technology and the growing trend for storing enterprise data in the cloud, globalisation has hit a major snag.